(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Caste has always been a very significant and decisive factor of Indian politics. It is a deep rooted feature of Indian social structure. Firstly its evidence showed in Manusmriti, a document that compiles the code of conduct for human society. The Varna system of ancient time now turned into caste system. The word caste has been derived from the Spanish word `CASTA` that means breed or race. The meaning of caste is, people belonging to same breed. It played a major role in Indian politics not only after independence but also in pre independence era. After caste based reservation, the importance of every caste increased and these are playing an important role in decision making process.